2022
DOI: 10.1038/s41541-022-00561-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of an AS03-adjuvanted plant-based SARS-CoV-2 vaccine in Adults with and without Comorbidities

Abstract: The rapid spread of SARS-CoV-2 continues to impact humanity on a global scale with rising total morbidity and mortality. Despite the development of several effective vaccines, new products are needed to supply ongoing demand and to fight variants. We report herein a pre-specified interim analysis of the phase 2 portion of a Phase 2/3, randomized, placebo-controlled trial of a coronavirus virus-like particle (CoVLP) vaccine candidate, produced in plants that displays the SARS-CoV-2 spike glycoprotein, adjuvante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Although Th2 skewing was initially considered a potential risk for SARS-CoV-2 vaccines and assessment of Th1/Th2 polarization was considered essential during early COVID-19 vaccine development 62,63 , to our knowledge no suggestion of VAED with or without a link to inappropriate Th2 responses has been observed with any SARS-CoV-2 vaccine 64 . In the case of CoVLP +AS03 specifically, there has been no suggestion of VAED in either a macaque challenge study 15 or in the clinical trials conducted to date despite the strong induction of both Th1-and Th2-type cytokine responses 33,40,65 . In fact, the IL-4 response elicited by the combination of CoVLP and AS03 may play an important role in the strength of the antibody responses observed, possibly by supporting follicular T-cell involvement and germinal center development [66][67][68][69] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Th2 skewing was initially considered a potential risk for SARS-CoV-2 vaccines and assessment of Th1/Th2 polarization was considered essential during early COVID-19 vaccine development 62,63 , to our knowledge no suggestion of VAED with or without a link to inappropriate Th2 responses has been observed with any SARS-CoV-2 vaccine 64 . In the case of CoVLP +AS03 specifically, there has been no suggestion of VAED in either a macaque challenge study 15 or in the clinical trials conducted to date despite the strong induction of both Th1-and Th2-type cytokine responses 33,40,65 . In fact, the IL-4 response elicited by the combination of CoVLP and AS03 may play an important role in the strength of the antibody responses observed, possibly by supporting follicular T-cell involvement and germinal center development [66][67][68][69] .…”
Section: Discussionmentioning
confidence: 99%
“…As previously described 65 , WHO International Standard anti-SARS-CoV-2 immunoglobulin (human; NIBSC code: 20/136) was included in antibody binding and neutralization assays for the purpose of facilitating comparison of results with other studies. This standard material is pooled plasma from eleven individuals who recovered from SARS-CoV-2 infection with very high NAb responses 35 .…”
Section: Standardization Of Antibody Titers With the Who 20/136 Poole...mentioning
confidence: 99%
“…For example, once the SARS-CoV-2 spike protein sequence became available, Medicago Inc. generated the VLP vaccine candidates in just 20 days [ 47 ]. Moreover, phase 1 randomized trials; the phase 2 portion of a phase 2/3 randomized, placebo-controlled studies; and phase 3, multinational, randomized, placebo-controlled trials have indicated that the SARS-CoV-2 spike glycoprotein VLP (CoVLP) expressed in Nicotiana benthamiana L. is highly immunogenic, well tolerated, and can effectively prevent COVID-19 [ 64 , 65 , 66 ].…”
Section: Overview Of the Present Landscape Of Plant-based Vaccinesmentioning
confidence: 99%
“…[ 111–113 ] Plant‐derived VLPs were also developed against Covid‐19 by transfecting N. benthamiana with full‐length S glycoprotein of SARS‐CoV‐2 and the vaccine nanoparticles were evaluated through different phases of clinical trials. [ 114–116 ] During phase 3, a total of 24,141 participants were intramuscularly vaccinated with a combination of the plant‐derived coronavirus‐like particles (CoVLP) and Adjuvant System 03 (AS03) or placebo, resulting in vaccine efficacy ranging from 69.5% in preventing any symptomatic Covid‐19 infection to 78.8% in preventing moderate‐to‐severe disease. In general, these studies suggest plant‐derived VLPs with anchored antigens on the surface are a promising vaccine candidate against various pathogens.…”
Section: Genetic Fusion Of Recombinant Antigens To Natural Self‐assem...mentioning
confidence: 99%